Talkin' Tar Heel : How Our Voices Tell the Story of North Carolina - Wolfram, Walt, 1941-; Reaser, Jeffrey, 1976- (Book collections on Project MUSE., 2014)
"Are you considered a "dingbatter," or outsider, when you visit the Outer Banks? Have you ever noticed a picture in your house hanging a little "sigogglin," or crooked? Do you enjoy spending time with your "buddyrow," or close friend? Drawing on over two decades of research and 3,000 recorded interviews from every corner of the state, Walt Wolfram and Jeffrey Reaser's lively book introduces readers to the unique regional, social, and ethnic dialects of North Carolina, as well as its major languages, including American Indian languages and Spanish. Considering how we speak as a reflection of our past and present, Wolfram and Reaser show how languages and dialects are a fascinating way to understand our state's rich and diverse cultural heritage. The book is enhanced by maps and illustrations and augmented by more than 100 audio and video recordings, which can be found online at talkintarheel.com."--